2022
DOI: 10.3390/cancers14133151
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Adnexal Reporting Data System (O-RADS) for Classifying Adnexal Masses: A Systematic Review and Meta-Analysis

Abstract: In this systematic review and meta-analysis, we aimed to assess the pooled diagnostic performance of the so-called Ovarian Adnexal Report Data System (O-RADS) for classifying adnexal masses using transvaginal ultrasound, a classification system that was introduced in 2020. We performed a search for studies reporting the use of the O-RADS system for classifying adnexal masses from January 2020 to April 2022 in several databases (Medline (PubMed), Google Scholar, Scopus, Cochrane, and Web of Science). We selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In contrast, among ORADS Grades 1,2 and 3, no major surgical procedure was carried out. Our observation was similar to observations by Jha et al [13] and Ahmed et al [14] who noted that patients with higher grades of ORADS had underwent invasive surgical procedures.…”
Section: Prognosis and Clinical Follow Upsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, among ORADS Grades 1,2 and 3, no major surgical procedure was carried out. Our observation was similar to observations by Jha et al [13] and Ahmed et al [14] who noted that patients with higher grades of ORADS had underwent invasive surgical procedures.…”
Section: Prognosis and Clinical Follow Upsupporting
confidence: 92%
“…The IOTA model was the most studied one till the advent of ORADS system. Basha et al [14] . Determined the malignancy rates, validity and reliability of the O-RADS approach when applied to a database of 647 adnexal masses collected before the development of the O-RADS system.…”
Section: Prognosis and Clinical Follow Upmentioning
confidence: 99%
“…A multicenter study [22] derived from 4905 masses for external validation of the O-RADS conducted that the O-RADS had 0.92 sensitivity and 0.80 specificity at the 10% risk threshold (O-RADS 4). A meta-analysis [15] involving 4634 adnexal masses from 11 studies showed that the sensitivity and specificity of the O-RADS were 0.97 and 0.77, respectively. Even though the overall diagnostic efficacy and sensitivity were good, relatively low specificity was still inevitable; in the study of Hiett et al, which only included 150 patients with adnexal masses and set the malignant risk threshold at 10% directly, the specificity was only 0.466 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the American College of Radiology (ACR) released the Ovarian-Adnexal Reporting and Data System (O-RADS) ultrasound lexicon [ 14 ] and consensus guideline of risk stratification and management [ 12 ], which provide a standardized ultrasound lexicon for adnexal lesions and associated management schemes for all risk categories. The current studies showed that the O-RADS had a high diagnostic sensitivity but relatively low specificity [ 15 17 ], which means that the O-RADS can misdiagnose some benign masses as malignant and lead to overtreatment. Some scholars have proposed that the acoustic shadowing should be included in O-RADS classification system to improve its performance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk strati cation proposed by IOTA SR and O-RADS has been prospectively and externally validated, their performance was found to vary signi cantly across different reported studies [3,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%